The Study of Transportation Jakarta and Their Problem (Tracing to Sustainable Transportation) - Perwira Sultan Kelana (IPEM 15 UMY 273, 2015)
*273 Congestion is prime problem for transportation in Jakarta and if we are not solving this problem as soon as possible, it will be bring the disadvantageous for everyone. Trough from this study, we will learn about the sustainability system which applied in Jakarta as a solution to reduce congestion in Jakarta. This research is qualitative research and technique of collecting data from this research is using interviewing data which taken by key informant. The respondent from this research is a head office division of traffic line program in Jakarta namely is Mr, Dodi Setiono. This division is a part which includes into unit of department transportation in Jakarta. They have important role to controlling traffic jam in Jakarta and have to solving their problem. Therefore Mr, Dodi setiono is a key informant in this research because he can explain about the problem and also solution to reduce congestion in Jakarta.